Use of uterine artery Doppler velocimetry values to predict pregnancy in intrauterine insemination cycles in couples with unexplained infertility - Kale, İbrahim and Dizdar, Merve (Journal of Surgery and Medicine, 2022)
Background/Aim: It is known that pregnancy success in IUI cycles performed in couples with unexplained infertility is below 20% even under the best conditions. Predicting the success in IUI cycles and directing patients to appropriate assisted reproductive treatment is essential for the time and budget. In this context, we aimed to investigate the use of uterine artery Doppler velocimetry values to predict pregnancy in intrauterine insemination (IUI) cycles in couples with unexplained infertility. Methods: In this prospective cohort study, couples with unexplained infertility were randomly assigned to two groups: clomiphene citrate (CC) and gonadotropin. The CC group used 50-150 mg CC daily between the 5th and 9th days of the menstrual period, while the gonadotropin group used 37.5-75 IU of recFSH daily from the 3rd day of the menstrual period until the dominant follicle developed. Ovulation was triggered by recHcg when at least one dominant follicle of 17 mm or larger was detected. Intrauterine insemination was performed 36 hours after the trigger. Uterine artery flow pulsatility index (PI), resistance index (RI)and the systolic-diastolic ratio (S/D) were measured in all patients by Doppler ultrasound on the 3rd day of menstruation and trigger day. Uterine artery Doppler values of the group that achieved pregnancy and those who could not conceive were compared as the main outcome of the study. Results: The study was designed over 143 IUI cycles, 89 cycles in the gonadotropin group and 54 cycles in the CC group. In 143 IUI cycles, 24 (16%) pregnancies were obtained, seven (12%) in the CC group and 17 (12%) in the gonadotropin group. In both CC and gonadotropin cycles, mean age, BMI, duration of infertility, hormone levels on the third day of menstruation, endometrial thickness on 3rd day of menstruation and on the trigger day, dominant follicle number and mean follicle diameter were similar in the pregnant and non-pregnant groups (P<0.05). There was no statistical difference in uterine artery Doppler values (RI, PI and S/D) measured neither on the 3rd day of the cycle nor on the trigger day between pregnant and non-pregnant groups in patients receiving CC or gonadotropin (P<0.05). Conclusion: Considering the hormonal changes in stimulated cycles or other factors that may have an impact on endometrial blood flow and endometrial receptivity, we think that only uterine artery Doppler velocity measurement values are not effective in predicting pregnancy success in CC or gonadotropin-induced IUI cycles.